Antibacterial and photocatalytic activity of copper oxide nanoparticles synthesized using Solanum lycopersicum leaf extract. (26th July 2018) - Vaidehi, D; Bhuvaneshwari, V; Bharathi, Devaraj; Sheetal, B Pavithra
Abstract: The present study was aimed to synthesis copper oxide nanoparticles by green chemistry method. Copper oxide nanoparticles (CuO–NPs) were synthesized using Solanum lycopersicum aqueous leaf extract. The synthesized CuO–NPs were characterized by UV–visible spectroscopy, Field emission-scanning electron microscopy (FE-SEM), High resolution-transmission electron microscopy (HR-TEM), Energy dispersive x-ray spectrometer (EDX), and Dynamic light scattering spectrometer (DLS). FE-SEM and TEM observation showed that the average size of 20–40 nm with spherical shape of CuO–NPs and the presence of phytochemicals which are responsible for reduction and stabilization were studied by FT-IR. XRD studies revealed the monocyclic crystalline phase of CuO–NPs. The synthesized CuO–NPs showed significant antibacterial activity against both Gram positive and Gram negative bacterial pathogens, assayed using agar well diffusion method and synthesized CuO–NPs induce significant morphological changes to bacterial pathogens, determined using FE-SEM. Furthermore, photocatalytic degradation of crystal violet (CV) under visible light irradiation using CuO–NPs was performed. Synthesized nanoparticles exhibited 97% degradation activity for CV. Overall our studies supported the eco-friendly, green synthesized CuO–NPs can be used as potential biocidal and photocatalytic agents.